Pengaruh Keefektifan Komite Audit Dan Profitabilitas Terhadap Jangka Waktu Pelaporan Keuanngan : (Studi Empris Pada Perusahaan â€“ Perusahaan Dalam Index LQ45) - Nurwis Nurwis; Hapsa Ediyamo; Karmila Rahayu; Baadia kelean; Daniel Fordatkosu; Jan Tomasoa (Trending: Jurnal Manajemen dan Ekonomi, 2023)
â€œThe Influence of Audit Committee Effectiveness and Profitability on Reporting Periodâ€ Finance in Companies in the LQ45 Index (2018-2021) Lecturer in Financial Statement Analysis Course (Christina Sososutiksno SE., M.Sc, Ak).This study aims to test and prove empirically regarding the influence of audit committee effectiveness and profitability on the financial reporting period.The population of this study is 45 companies in the LQ45 Index listed on the Indonesia Stock Exchange 2018-2021 and 27 companies that meet the criteria as a sample, so that the number of observations analyzed becomes 108. The analysis technique used is multiple regression with a tool analysis of IBM SPSS Statistics 23.The results of the analysis show that the audit committee effectiveness variable has no significant effect on the financial reporting period, while the profitability variable has a significant effect on the financial reporting period.